Characteristics and Breakdown Behaviors of Polysilicon Resistors for High Voltage Applications - Xiao-Yu Tang; Ke Dong (Advances in Condensed Matter Physics)
With the rapid development of the power integrated circuit technology, polysilicon resistors have been widely used not only in traditional CMOS circuits, but also in the high voltage applications. However, there have been few detailed reports about the polysilicon resistors’ characteristics, like voltage and temperature coefficients and breakdown behaviors which are critical parameters of high voltage applications. In this study, we experimentally find that the resistance of the polysilicon resistor with a relatively low doping concentration shows negative voltage and temperature coefficients, while that of the polysilicon resistor with a high doping concentration has positive voltage and temperature coefficients. Moreover, from the experimental results of breakdown voltages of the polysilicon resistors, it could be deduced that the breakdown of polysilicon resistors is thermally rather than electrically induced. We also proposed to add an N-type well underneath the oxide to increase the breakdown voltage in the vertical direction when the substrate is P-type doped.